Analisis Minimisasi Biaya Amlodipin Generik dan Bermerk pada Pengobatan Hipertensi di RS X Pekanbaru Tahun 2015 - Merliana, Hanny; Sjaaf, Amal Chalik (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Hypertension in a big challenge in Indonesia, proven by its prevalence that reached 25% in 2013 and conditions that mostly found in primary health care. In addition, hypertension management is considered to be suboptimal despite the availability of effective drugs. Amlodipine is one of anti-hypertensive that is commonly prescribed by X Hospital, Pekan Baru. Therefore, it is important to do cost minimization analysis to compare both generic and branded Amlodipine as an implementation of cost and quality control. This retrospective study involved early and medium stage of hypertensive patients that have at least a month period of treatment from January to December 2015 using provider’s perspectives of CMA (Cost Minimization Analysis). The result showed that generic form of Amlodipine is the most common anti-hypertensive drugs prescribed in Cardiology and Internal Medicine Clinic, X Hospital. It was suggested that average cost of generic form of Amlodipine was IDR 68.660 while branded one was IDR 374.844 or approximately 5.4 times higher. Both generic and branded Amlodipine significantly reduced blood pressure, but there was not any distinguish effect between them. It was concluded that generic form of Amlodipine was a less expensive and efficient choice in reducing blood pressure.